The Amphipoda of Sea City, Kuwait.—The Senticaudata (Crustacea) - Myers, Alan A.; Nithyanandan, Manickam (Zootaxa, 2016)
Thirteen species of Amphipoda Senticaudata were collected in Sea City, Kuwait using a Van Veen grab and an Ocklemann sledge. Of these seven species were new to science and are described and figured in this contribution.